Effect of Chicken Type and Reactor Temperature on Biofuel Yields from Pyrolysis of Poultry Litter - Okekunle, Pious O.; Itabiyi, Olukunle E.; Olafimihan, Emmanuel O.; Alayande, Ibraheem O.; Najeemdeen, Mutiu O.; Adisa, Omotolani A.; Popoola, Adedapo B. (European Scientific Journal, ESJ, 2019)
Efficient management of poultry litter resulting from the ever growing agricultural industry is key to saving the global environment. In this study, effect of chicken type and reactor temperature on biofuel yields from pyrolysis of poultry litter has been studied. Samples of fresh droppings of broiler and layer chickens were collected from the poultry farm of Ladoke Akintola University of Technology, Ogbomoso, South-Western Nigeria. The samples were sun dried for two days and afterwards oven-dried at a temperature of 105 oC for 10 minutes. Samples of 40 g each were pyrolyzed at four different reactor temperatures (300, 400, 500 and 600 oC) for 15 minutes. The yield of pyro-oil and pyro-gas from the litter of the two chicken types increased with reactor temperature while char yield decreased with it. Pyro-oil yield from broiler litter was higher than that from layer litter at all temperatures while pyro-gas yield from layer litter was higher than that from broiler litter at all the conditions studied. The highest yield of pyro-oil (65.10% at 600 oC) was obtained from broiler litter while the highest yields of char (42.12% at 300 oC) and pyro-gas (25.7% at 600 oC) were recorded for layer litter. The presence of alkali metals in different proportions in broiler and layer litter was identified to have influenced pyrolysissecondary reactions. Cellulose, hemicellulose and lignin may also be in different percentages in the two types of chicken litter.